I am every good thing - Barnes, Derrick; James, Gordon C. (New York : Nancy Paulsen Books, 2020)
The confident Black narrator of this book is proud of everything that makes him who he is. He's got big plans, and no doubt he'll see them through--as he's creative, adventurous, smart, funny, and a good friend. Sometimes he falls, but he always gets back up. And other times he's afraid, because he's so often misunderstood and called what he is not. So slow down and really look and listen, when somebody tells you--and shows you--who they are. There are superheroes in our midst.
School Library Journal starred, August 2020
3.6.
K-3.
AD610L
Keywords: Character -- Juvenile fiction; Self-esteem in children -- Juvenile fiction; African American children -- Juvenile fiction; Self-confidence -- Fiction; Character -- Fiction; Self-esteem -- Fiction; African Americans -- Fiction